2020
DOI: 10.47338/jns.v9.549
|View full text |Cite
|
Sign up to set email alerts
|

Bone cutter versus plastibell device in neonatal circumcision: A randomized trial

Abstract: Background: Several techniques and devices have been described for circumcision each with its own pros and cons. The objective of this study was to compare the outcome of neonatal circumcision between bone-cutter and plastibell devices at our institution. Methods: This is a randomized trial (unregistered) conducted at the Pediatric Surgical Unit of a tertiary teaching hospital situated in a semi-urban setting, between January 2019 and December 2019. The uncircumcised neonates underwent circumcision by either b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Many studies suggested that plastibel circumcision is a simple method and minor complications include local sepsis, bleeding, bell impaction, dysuria, incomplete separation of plastibel device, proximal migration of the ring, and excessive or inadequate skin removal. 13,14,16 In our study, we did not encounter any of the complications mentioned earlier.…”
Section: Discussionmentioning
confidence: 47%
“…Many studies suggested that plastibel circumcision is a simple method and minor complications include local sepsis, bleeding, bell impaction, dysuria, incomplete separation of plastibel device, proximal migration of the ring, and excessive or inadequate skin removal. 13,14,16 In our study, we did not encounter any of the complications mentioned earlier.…”
Section: Discussionmentioning
confidence: 47%